Social mobility of Roma from a decolonization perspective: Introduction to the thematic issue of Romano džaniben. - Ort, Jan (Romano džaniben, 2023)
The editorial for the thematic issue presents the focus on Romani social mobility not as an interest in the individual stories of Roma, but rather in the ways in which such mobility is framed and understood by Roma themselves. This, according to the author, leads to a connection to postcolonial theory as a critique of established discourses and power structures, and subsequently to decolonization as a way of taking control of the production of knowledge about the Roma by the Roma themselves. The author here emphasizes the necessity of connecting these emphases to the context of the Central and Eastern European region, but also to the different conditions within it. Above all, however, he asks how to extend the project of decolonization beyond academic circles so that it does not represent another way of reproducing established power structures.